Traumatic anterior hip dislocation with associated bilateral femoral fractures in a child: a case report and review of the literature - Cao, Zongbing (Pan Afr Med J, 2019)
Traumatic anterior hip dislocation is rare, because the hip joint is a highly stable joint. It is extremely rare for the anterior hip dislocation with combined bilateral femoral fracture in children. We present a case of 7-year-old boy with traumatic anterior hip dislocation with associated bilateral femoral fractures. Radiographic examination showed the right femoral head was dislocated anteroinferiorly. The ipsilateral femoral shaft showed a transverse femoral shaft fracture and proximal and distal femoral bifocal fractures of the contralateral femur. The dislocation of the right hip was reduced 10 hours after the injury in local hospital. One week later, the right femoral shaft fracture and left proximal femoral fracture were open reduced and internally fixed with plate and screws and the distal left femoral fracture was closed reduced and fixed with Kirschner wires. Postoperatively, active hip flexion and extension to recover hip and knee movement were then permitted but without weight bearing for 3 months. Radiographs at 3 months, at 6 months showed the fractures healed well and hardware were removed respectively. However, irregularities of the femoral head meaned avascular necrosis of the femoral head. This case stresses the importance of a rapid evaluation and treatment for the dislocation of the hip, providing a stable reduction and a firm internal fixation of the associated fractures.